Kritik Sosial dan Benturan Budaya dalam Novel Salah Asuhan Karya Abdoel Moeis - Nurul Aisyah; Tiara Altaskia; Winda Sofri Yanti; Abdurahman . (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
Salah Asuhan, a novel by Abdoel Moeis, is an important work in Indonesian literature that explores the conflict between Eastern and Western cultures during the Dutch colonial period. The story centers on Hanafi, a native Indonesian who is educated in Western ways and becomes obsessed with adopting European culture. As a result, he rejects his own cultural identity, leading to inner conflict, social alienation, and failure in his personal relationships, including his marriage. Through this narrative, the author highlights the negative consequences of blindly imitating foreign cultures without understanding one’s own roots. The novel also serves as a critique of colonial influence on the mindset of indigenous people. Therefore, Salah Asuhan is not only a literary work but also a moral lesson about the importance of maintaining cultural identity, being selective in accepting external influences, and appreciating one’s own heritage.